(untitled) (London Journal of Research In Science: Natural and Formal, 2023)
Drought is a serious problem in Karnataka, which is predominantly a 60 to 70% dry farming state. The development of any micro, mini, sub, or watershed area using a different approach is only the key solution, and it is no longer a secret. The village of Gudumadanahalli is separated into sections depending on the origin and flow direction of water drains / streams. Water harvesting and drainage line treatment buildings were discovered using a study of topo-sheet and LANDSAT images of the region, as well as other parameters such as soil type, slope type, land use / cover, waste lands, hydro-morphology, forest cover, command area, and so on. Prioritization is important in identifying groundwater potential that requires immediate attention so that it can be developed with available resources. An attempt has been made to prioritise the study area based on several criteria, with the total weightage of marks given in the table. Data for these criteria were generated using remote sensing, GIS, and other resources. The study also demonstrates that when remote sensing and GIS are used in tandem, they provide ample scope for the integration of spatial and non-spatial data, which can be successfully used to prioritise any of the watersheds in a more scientific and unbiased manner.